Input-output data and service outsourcing. A reply to Dietrich, McCarthy and Anagnostou - Giuseppe Vittucci Marzetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
In a recent paper, McCarthy and Anagnostou (2004, The impact of outsourcing on the transaction costs and boundaries of manufacturing, International Journal of Production Economics, 88, pp. 61-71) use a decomposition approach put forward by Dietrich (1999, Explaining economic restructuring: an input-output analysis of organisational change in the European Union, International Review of Applied Economics, 13(2), pp. 219-40) to analyze the impact of contracting-out in the UK manufacturing decline over the '80s and the '90s. Dietrich claims that this decomposition can distinguish the part of the manufacturing output decrease produced by the increased integration of services in manufacturing from the one which is instead produced by final demand-related changes. This paper aims at critically examining Dietrich's decomposition approach and showing its flaws. In so doing, the paper also carefully analyzes the changes outsourcing produces in input-output tables. Thus, it might prove useful also in avoiding further mistakes in using input-output analysis for studying outsourcing-related changes in economic structure.
Keywords: 330